A Volatility Spillover Analysis Between Bond and Commodity Markets as an Indicator for Global Liquidity Risk - Kırkpınar, Aysegul; Evrim Mandacı, Pınar (Panoeconomicus, 2023)
This study aims to analyze the volatility spillover between bond and commodity markets in terms of global liquidity risk. The data covers the daily closing prices of bond markets in specified countries - Brazil, Russia, India, China, and Turkey - and certain commodities - gold and oil - for the period January 2008 to January 2022. We utilized the DCC-GARCH model to analyze volatility spillover between these markets and the Copula DCC-GACRH model to determine dependence structures between them. Additionally, we applied the Hong Causality in Variance Test to determine the direction of the causal relationships between these markets. Our empirical findings indicate the existence of significant volatility spillovers between gold and most of these bond markets (Brazil, China, Russia, and Turkey), and between oil and some of these bond markets (Russia, India and Turkey). Our results indicate a limited diversification benefit for investors and portfolio managers. JEL: G10, G15, C32.